The influence of soft skills on the work readiness of students in the Faculty of Economics and Business at Muhammadiyah University Makassar - Awal Syam (www.amertainstitute.com, 2025)
This study is a quantitative study that aims to determine the effect of soft skills on the work readiness of students at the Faculty of Economics and Business, Muhammadiyah University Makassar. The data used is primary data collected through the distribution of questionnaires using a Likert scale as a measurement instrument. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 25, employing simple linear regression techniques to test the influence of independent variables on dependent variables. The results showed that soft skills had a positive and significant effect on students' work readiness, with a t-value of 2.502 > t-table 1.663 and a significance value of 0.014 < 0.05. These findings confirm that personality aspects play an important role in preparing students for the world of work. The implications of this study encourage higher education institutions to develop integrated coaching programs that strengthen soft skills as part of efforts to improve graduate work readiness.